116 An Assessment of Current Practice for Suspected Paediatric Testicular Torsion. (12th October 2021) - Gibb, J; Babawale, O; Hodgson, D; Harrison, R
Abstract: Aim: British Paediatric surgery guidelines (2019) state 'immediate surgery should be performed if testicular torsion is suspected'. However, imaging 'may be considered for a small number of children under the guidance of a senior clinician in late presenters or in those with atypical features. This study reviewed current practice in our hospital. Method: Boys aged 16 and under in 2017-2019 who underwent scrotal exploration for suspected testicular torsion were reviewed. Outcomes assessed were number having ultrasound prior to theatre, pathological findings, number who had an orchidectomy, and post-op complications. Additionally, all testicular ultrasounds in those aged under 16 were screened to establish how many were requested for possible or missed torsion. Results: 46 patients underwent surgical exploration of which 18 had a confirmed torsion. Six patients had imaging prior to surgery, of which five suggested torsions and four of these were confirmed in theatre. 202 boys under 16 had a testicular ultrasound; 26 of these were for late presentation or those with atypical features of torsion. Three underwent scrotal exploration two of whom had reports suggestive of torsion which was confirmed on exploration. Conclusions: Most testicular torsions occur around the age of puberty with no torsion identified in patients under 10. Ultrasound is a useful tool for identification of vascularity or alternative pathology in late or atypical presentations of torsion; but does not replace clinical judgement. Imaging may have prevented unnecessary exploration in 23 cases, although negative imaging did not always preclude exploration.